Mechanisms underlying the beneficial effects of Kaiyu Granule for depression - Jin, Xi (Medknow Publications & Media Pvt Ltd, 2013)
The proprietary Chinese medicine preparation Kaiyu Granule is made of bupleurum, nutgrass galingale rhizome, szechwan lovage rhizome, turmeric root tuber, white peony alba, cape jasmine fruit, fried semen ziziphi jujubae, and prepared liquorice root. It is a common recipe for the clinical treatment of depression in China. In this study, after 21 days of unpredictable stress exposure, Wistar rats exhibited similar behavioral changes to patients with depression. Moreover, G-protein-coupled inwardly rectifying K(+) channel 1 mRNA and protein expression were significantly reduced in rat hippocampal CA1 and CA3 regions. However, G-protein-coupled inwardly rectifying K(+) channel 1 mRNA, protein expression, and rat behavior were clearly better after administration of 12, 8, or 4 g/kg of Kaiyu Granule when depression model rats underwent stress. 12 g/kg of Kaiyu Granule had the most obvious effects on the increased expression of G-protein-coupled inwardly rectifying K(+) channel 1 mRNA and protein in rat hippocampal CA1 and CA3 regions. These results suggested that Kaiyu Granule improved depression by affecting G-protein-coupled inwardly rectifying K(+) channel 1 expression in the rat hippocampus.